The use of highmolecular-weight hyaluronic acid in the treatment of osteoarthritis - S. G. Anikin (Современная ревматология)
Osteoarthritis (OA) is one of the most common diseases of the musculoskeletal system, affecting mainly people of old age. The management of OA requires combined therapy using pharmaceutical and nonpharmacological modalities, including hyaluronic acid (HA). Hylans are highmolecular-weight (HMW) HA derivatives. The use of hylans results in reducing pain and stiffness and in improving functional activity. Their efficacy is comparable with that of lowmolecular-weight HA. Intraarticular injection of HMW HA derivatives is safe and effective for treating OA.